A Critical Review of the Book Quantitative Data Analysis for Language Assessment (Fundamental Techniques and Advanced Methods) - Rajab Esfandiari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Given the significant role of quantitative data in theory building in language assessment, the need for a book covering data analysis methods is strongly felt. The two-volume book, Quantitative Data Analysis for Language Assessment (Fundamental Techniques and Advanced Methods), edited by Vahid Aryadoust and Michelle Raquel and published by Routledge fills this gap. The first volume entitled Quantitative Data Analysis for Language Assessment: Fundamental Techniques was published in 2019, and the second volume by the title of Quantitative Data Analysis for Language Assessment: Advanced methods was published in 2020. The present study is critical in goal, qualitative in methodology, and emergent in analysis. The book is comprehensive in scope and content, includes high-quality, well-written chapters follows a coherent style of writing, and is rich in the number of quantitative data analysis methods. The book has some limitations, including inexplicitness of criteria for selection of quantitative data methods and failure to include more common traditional methods. The book can generate further research in this subfield of applied linguistics, expand the subfield, and contribute to theory building in language assessment. Postgraduate students, L2 assessment practitioners, and researchers are strongly advised to read this invaluable edited book.